2002
DOI: 10.1176/appi.ajp.159.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of CSF Tau Levels and [123I]Iodoamphetamine SPECT in Mild Cognitive Impairment: Implications for a Novel Predictor of Alzheimer’s Disease

Abstract: The CSF-CBF index is useful in predicting Alzheimer's disease in subjects with mild cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 8 publications
5
55
0
3
Order By: Relevance
“…This is in accordance with the majority of previous studies, showing that functional abnormalities in the parietal cortex have the highest predictive values for the future development of AD compared to other brain regions [1,6,8,[18][19][20]25]. However, this is not an unequivocal finding as some other studies have suggested that decreased rCBF in the posterior cingulated gyrus is superior in detecting incipient AD among subjects with MCI [22,23,27].The reason for this discrepancy is unknown, although differences in instrumentation and variations in the affection of brain areas in this heterogeneous population of subjects with MCI may be possible explanations. From a methodological point of view, the predictive accuracy of cortical rCBF obtained with the present 133 Xe method was very similar to previously reported SPECT studies [6,[18][19][20].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in accordance with the majority of previous studies, showing that functional abnormalities in the parietal cortex have the highest predictive values for the future development of AD compared to other brain regions [1,6,8,[18][19][20]25]. However, this is not an unequivocal finding as some other studies have suggested that decreased rCBF in the posterior cingulated gyrus is superior in detecting incipient AD among subjects with MCI [22,23,27].The reason for this discrepancy is unknown, although differences in instrumentation and variations in the affection of brain areas in this heterogeneous population of subjects with MCI may be possible explanations. From a methodological point of view, the predictive accuracy of cortical rCBF obtained with the present 133 Xe method was very similar to previously reported SPECT studies [6,[18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…Despite these possibilities, only little is known about the added diagnostic value of combining different biomarkers [27]. This article provides proof of principle that a combination of rCBF and CSF biomarkers clearly improves the risk assessment of future AD in subjects with MCI.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a few studies that have examined rCBF or rCMRglc changes in populations with cognitive deficits (at high risk for AD but not yet demented) (Arnaiz et al, 2001;Berent et al, 1999;De Santi et al, 2001;Minoshima et al, 1997;Okamura et al, 2002;Ouchi et al, 1998;Pietrini et al, 1993), reduced rCMRglc of the hippocampal formation (De Santi et al, 2001;Ouchi et al, 1998) has been reported. Reduced rCBF or rCMRglc in the temporal neocortex (Arnaiz et al, 2001;Berent et al, 1999;Pietrini et al, 1993) and posterior cingulate (Minoshima et al, 1997;Okamura et al, 2002) has been reported to predict conversion to AD.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced rCBF or rCMRglc in the temporal neocortex (Arnaiz et al, 2001;Berent et al, 1999;Pietrini et al, 1993) and posterior cingulate (Minoshima et al, 1997;Okamura et al, 2002) has been reported to predict conversion to AD. Only one study (Johnson et al, 1998) used multivariate techniques to examine resting flow in questionable AD.…”
Section: Introductionmentioning
confidence: 99%